A uniform field ion mobility study of melittin and implications of low‐field mobility for resolving fine cross‐sectional detail in peptide and protein experiments. Issue 16 (5th June 2015) - May, Jody C.; McLean, John A.; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> An experimental investigation of protonated melittin was undertaken using uniform field ion mobility‐mass spectrometry (IM‐MS) to measure helium‐based collision cross sections (CCS). Upon varying the electrospray solvent from aqueous to methanol, the [M + 2H]2+ species was observed to shift from a compact to an extended CCS, suggesting a gas‐phase structural transition which depends on initial solvent conditions. The [M + 3H]3+, [M + 4H]4+, and [M + 5H]5+ species exhibited peak broadening in response to the organic solvent, but retained their CCS, suggesting these are locked into a stable gas‐phase structure. The CCS of the stable [M + 3H]3+ and [M + 4H]4+ species were found to be similar, suggesting these ions adopt structurally similar features in the gas phase, which, based on previous studies, likely retains α‐helical characteristics. We also report on the resolution of additional low‐abundance ion mobility peak features which are sensitive to the magnitude of the drift field. We observe a loss in the peptide ion mobility resolution above ca. eight Townsends, suggesting that the ability to resolve subtle structural details is inherently related to conducting ion mobility measurements at low field and under conditions which minimize ion heating.